The baby bunny - Hillert, Margaret; Masheris, Robert (Parsippany, NJ : Modern Curriculum Press, 1981)
Easy-to-read text follows the growth, antics, and adventures of a baby bunny.
1.4
K-3
Keywords: Rabbits -- Fiction